Designing of Cylindrical Concrete Tanks with Regard to Buckling and Second Order Effects. (2017) - Halicka, Anna; Podgórski, Jerzy
Abstract: Structural designing of reinforced concrete structures consists in determination of the cross section height and amount of the vertical and horizontal reinforcement on the basis of the internal forces. These forces are not determined correctly without considering the structure deformation. It means that the geometric type nonlinearity should be regarded at least. In the case of compression the buckling and the so called "second order effects" should be taken into account. The EC2-1-1 code gives the general rules for such effects, but they are described in details only for columns and buildings. Therefore the aim of this paper is to formulate recommendations which will be useful for reinforced concrete cylindrical tanks for liquids and particulate solids compressed vertically (meridional compression) and horizontally (hoop compression). These recommendations are formulated on the basis of nonlinear FEM analysis, which is preceded by analysis of expressions describing the critical stress of cylinders, formulated by theory of elasticity.